2019
DOI: 10.5607/en.2019.28.1.119
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Proven Case of CSF1R-mutant Adult-onset Leukoencephalopathy with Axonal Spheroids and Pigmented Glia (ALSP) with Premature Ovarian Failure

Abstract: Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) is a progressive degenerative white matter disorder caused by mutations in the tyrosine kinase domain of the CSF1R gene. ALSP is often misdiagnosed as other diseases due to its rarity and various clinical presentations such as Parkinsonism, pyramidal signs, cognitive impairment and/or psychiatric symptoms. We describe an autopsy case of ALSP with a CSF1R mutation. A 61-year-old woman pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Females tend to be more severely affected by CRL and exhibit a higher prevalence of gait disorders (5). Furthermore, ataxia and cerebellar involvement have also been reported predominantly in female CRL patients (13 out of 15 documented cases) (42,45,(47)(48)(49)(50)(51)(52)(53)(54)(55). These findings raise the possibility that estrogens and/or androgens might specifically regulate subpopulations of microglia such as the cerebellar microglia, or those interacting with motor neurons.…”
Section: Discussionmentioning
confidence: 97%
“…Females tend to be more severely affected by CRL and exhibit a higher prevalence of gait disorders (5). Furthermore, ataxia and cerebellar involvement have also been reported predominantly in female CRL patients (13 out of 15 documented cases) (42,45,(47)(48)(49)(50)(51)(52)(53)(54)(55). These findings raise the possibility that estrogens and/or androgens might specifically regulate subpopulations of microglia such as the cerebellar microglia, or those interacting with motor neurons.…”
Section: Discussionmentioning
confidence: 97%
“…Expression of the CSF1R signaling ligands CSF-1 (predominant in the cerebellum) and interleukin (IL)-34 (predominant in the cortex) are important for microglial homeostasis in both mice and humans, indicating brain region-specific effects [ 29 ]. It is acknowledged that CSF1R -related leukoencephalopathy is caused by dysfunctional microglia, and that different mutation locations of the CSF1R gene lead to different clinical phenotypes of CSF1R -related leukoencephalopathy, with both disease presentation and progression varying significantly among family members [ 30 , 31 ]. Although CSF1R -related leukoencephalopathy is a genetic disease inherited in an autosomal dominant pattern, approximately 36% of cases are sporadic [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological features of CSF1R -related leukoencephalopathy include a widespread loss of myelin and axons, astrogliosis and macrophage accumulation in the presence of swollen and spherical axons [ 31 ]. Microglia are adapted to the CNS microenvironment and express specific gene signatures ( P2ry12 , Tmem119 and SiglecH ) in order to perform tissue-specific functions [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] The loss of fertility and the clinical effects of low estrogen are two important consequences of POF. [ 2 ] There are many factors that cause POF, including autoimmune disease, chemotherapy, and some gene mutations, and it is believed that it is mainly related to permanent damage to the ovaries. [ 3,4 ] Recently, research has shown that approximately 30% of POF cases are related to immune abnormalities.…”
Section: Introductionmentioning
confidence: 99%